Strategies of Elimination: “Exempted” Aborigines, “Competent” Indians, and Twentieth-Century Assimilation Policies in Australia and the United States - Ellinghaus, Katherine (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2007)
AbstractDespite their different politics, populations and histories, there are some striking similarities between the indigenous assimilation policies enacted by the United States and Australia. These parallels reveal much about the harsh practicalities behind the rhetoric of humanitarian uplift, civilization and cultural assimilation that existed in these settler nations. This article compares legislation which provided assimilative pathways to Aborigines and Native Americans whom white officials perceived to be acculturated. Some Aboriginal people were offered certificates of “exemption” which freed them from the legal restrictions on Aboriginal people’s movement, place of abode, ability to purchase alcohol, and other controls. Similarly, Native Americans could be awarded a fee patent which declared them “competent.” This patent discontinued government guardianship over them and allowed them to sell, deed, and pay taxes on their lands. I scrutinize the Board that was sent to Oklahoma to examine the Cheyenne and Arapaho for competency in January and February 1917, and the New South Wales Aborigines’ Welfare Board, which combined the awarding of exemption certificates with their efforts to assimilate Koori people into Australian society in the 1940s and 1950s. These case studies reveal that people of mixed white/indigenous descent were more likely to be declared competent or exempt. Thus, hand in hand with efforts to culturally assimilate Aborigines and Native Americans came attempts to reduce the size of indigenous populations and their landholdings by releasing people of mixed descent from government control, and no longer officially recognizing their indigenous identity.